2015
DOI: 10.1016/s2214-109x(15)00144-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a community-led sanitation intervention on child diarrhoea and child growth in rural Mali: a cluster-randomised controlled trial

Abstract: Bill & Melinda Gates Foundation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
452
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 327 publications
(485 citation statements)
references
References 26 publications
26
452
7
Order By: Relevance
“…Especially open-defecation in close proximity to the households, which probably serves as the main source for infections and transmission via flies, plummeted in both adults (before: 75.0%, after: 16.7%) and children (before: 78.3%, after: 4.5%). Similarly to findings from a CLTS trial in rural Mali [13], household heads from intervention communities significantly more often reported washing hands after defecating. The intervention significantly increased perceptions of open defecation as polluting the environment among beneficiary communities.…”
Section: Impact On Behaviour and Attitudessupporting
confidence: 53%
See 2 more Smart Citations
“…Especially open-defecation in close proximity to the households, which probably serves as the main source for infections and transmission via flies, plummeted in both adults (before: 75.0%, after: 16.7%) and children (before: 78.3%, after: 4.5%). Similarly to findings from a CLTS trial in rural Mali [13], household heads from intervention communities significantly more often reported washing hands after defecating. The intervention significantly increased perceptions of open defecation as polluting the environment among beneficiary communities.…”
Section: Impact On Behaviour and Attitudessupporting
confidence: 53%
“…Over the past decade, CLTS as a means to prevent diarrhoeal diseases has gained traction and is being applied at large scale in various low-and middle-income countries [22,35]. Yet, there is relatively little scientific inquiry about the specific effects of CLTS alone or in combination with other interventions against neglected tropical diseases [13,[36][37][38][39], and hence, the public health impact of CLTS [40]. We discuss the effect of an integrated package of interventions, placing emphasis on latrine construction by the community, levels of helminth and intestinal protozoa infections, infection patterns at follow-up and people's behaviour and attitudes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.Literature in the medical and epidemiological fields link poor sanitation to poor nutritional outcomes and child height (Pickering, Djebbari, Lopez, Coulibaly, & Alzua, 2015) through diarrhoea (Checkley et al, 2004), intestinal parasites (Esrey, Potash, Roberts, & Shiff, 1991), and environmental enteropathy (Humphrey, 2009). A meta-analysis conducted by Gertler et al (2015) uses experimentally-induced variation in open defecation to identify a causal effect of open defecation on child height.…”
Section: Notesmentioning
confidence: 99%
“…A previous pilot study in Côte d'Ivoire revealed that CLTS coupled with health education and preventive chemotherapy has the potential to decrease the incidence of helminth and intestinal protozoa infection, though heterogeneity from one community to another rendered interpretation of the results somewhat difficult [32]. Notwithstanding, a recent cluster randomised study in Mali found no effect of CLTS on diarrhoea 18 months after implementation of the intervention, but a significant beneficial effect on children's anthropometric measures, as children from the intervention group were significantly less stunted [59]. Of note, the authors used a cross-sectional design for assessing diarrhoea incidence at two time points (baseline and endline).…”
Section: Dissemination Of Key Findingsmentioning
confidence: 99%